REGULATION OF TILLERING IN WHEAT AND ITS RELATIONSHIP WITH GRAIN YIELD 2. CONTRIBUTION PERCENTAGES OF THE MAIN STEM AND PRIMARY TILLERS IN THE NUMBER OF SPIKELET AND GRAIN NUMBER AND WEIGHT OF 1000 GRAINS. - Al- Hassan, Mahmood & (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A Factorial experiment were conducted at the experimental farm of Field Crop College of Agriculture University of Baghdad Jadiria the winter Season of 2014-2015. This study was aimed to investigate the effect of seeding rates and nitrogen levels on Regulation of tillering in wheat and its relationship with grain yield and it’s components. Treatments were distributed in Factorial experiment within Randomized Complete Black Design (RCBD) with three replicates and with four seeding rates (60,80,100 and 120 kg.ha-1) and fertilized with four nitrogen levels (50,100,150 and 200 kgN.ha-1). The results showed that there were significant differences between two factors of study and their interaction on the number of spiklet, grain number and 1000 grain weight during the growing season. Main stem produced the highest average of spiklet number 19.23 spiklet.spike-1, grain number 46.82 grain.spike-1 and 1000 grain weight 41.739 compared to other primary tillers (tiller1,tiller2,tiller3). Concerning the seeding rate 60 kg.ha-1 resulted in the highest average of spiklet number 16.24 spiklet.spike-1, grain number 32.95 grain.spike-1 and 1000 grain weight 27.52 compared to other seed rates. The N level 100 kg.ha-1 gave the highest average of spiklet number 16.49 spiklet.spike-1, grain number 32.95 grain.spike-1 and 1000 grain weight 27.52 compared to other N levels. The Main Stem and Primary Tillers contribution Differed in the Number of Spiklet, Grain Number and 1000 grain weight between the factors of study, where the percentage contribution of main stem 31.65, 38.26 and 37.28 % respectively compared to the tillers (tiller1, tiller2, tiller3) which amounted to 27.43, 24.79 and 16.14 % respectively in the spiklets number, 28.00, 23.36 and 10.38 % respectively in grains number and 31.80, 20.37 and 10.56 % respectively in 1000 grain weight. We conclude that the total contribution of the primary tillers percentages in the Number of Spiklet, Grain Number and 1000 grain weight Exceeds the contribution of main stem an increase of 53.69 and 38.03 and 40.56 % respectively within two factors of study.